Validación del método analítico por espectrofotometríauv/vispara la cuantificación de risperidona en tabletas 2 mg - Escobar Vásquez, Gladys Fiorella (2013)
The analytical method validation is an integral part of the quality control system, since it gives reliability to the analytical results obtained in a laboratory, to ensure that a drug comply established equality parameters. We present the validation of an analytical method for quantification of 2 mg Risperidone tablets, using the technique of spectrophotometry UV / VIS proposed by the authors G. Alagumanivasagam, A. Anton Smith, Department of Pharmacy, Annamalai University in India.For the analysis of 2 mg Risperidone tablets from three pharmaceutical laboratories (Farmindustria, Marfan and Medrock) methanol was used as solvent and was measured at a wavelength of maximum absorbance of 278 nm.The samples were subjected to acid degradation, alkaline oxidation and thermolysis, obtaining interference less than 2%. The linearity test method showed a correlation coefficient of 0.9998910. For accuracy, the recovery rate was 99.65%, for the Cochran's Gtable less than Gexp was obtained (0.5330 <0.6830) and the Student t test statistic was obtained ttable less than texp (0.9028 <2.1448), for which accuracy complied according to their respective specifications. For the repeatability of the system CV of 0.121% was yielded. For the repeatability of the method CV of 0.250% was yielded. For intermediate precision CV between an analyst and the other was of 1.50%.The validation parameters determined lead to a validated analytical method proposed by the authors.